TRANSLATION OF SAPARDI DJOKO DAMONO’S POEM INTO ENGLISH - Ary Fadjar Isdiati (Department of English Education, Universitas Panca Sakti Bekasi, 2020)
This article describes the translation strategy used by John H. McGlynn to translate Sapardi Djoko Damono's poem Sajak Orang Gila into English with the title Ballad of a Crazy Man, and see: Has this translation’s poem equality in word level. If not, what is the cause. The method is descriptive qualitative. Data sources are the poem Sajak Orang Gila and Ballad of a Crazy Man. Words, phrases, and sentences in all the stanzas and lines were analyzed using the poetry translation theory by Andre Lavefere to determine the translation strategies used to translate the poem, and using the theory of the cause of inequality by Mona Baker. The analysis shows that the translation strategy used by John H. McGlynn are literal and interpretation translation strategy. The literal translation strategy is used to translate 11 stanzas, and the interpretation translation strategy is used to translate 2 stanzas. In general, the translation of this poem is good, because the meaning in the source poem is conveyed well in the target poem. However, in the translation of some stanzas found incompatible meanings in words. There are 3 causes of discrepancies found, namely: 1) Differences in physical or interpersonal perspectives; 2) The target language lack a special term (hyponym); and 3) Differences in expressive meaning.